THE INDUSTRIAL ORGANIZATION MANAGEMENT IN TERMS OF THE DIGITAL ECONOMY - H. Panflova (Publishing House of the State University of Management, 2018)
The article considers the industrial organization management issues in the context of the implementation concept «Industry 4.0». The overview of key production and information technologies, providing a competitive advantage for an industrial or-ganization in the field of digitalization, has given. The necessary conditions for the ef-fective interaction of service and production units within the production company on the base of the Internet of things, additive production and reverse engineering have spec-ified. Methodical recommendations on the organization and control of production pro-cesses, based on the concept of lean production and cross-sectoral cooperation in an in-dustrial organization have given.